(untitled) (Baghdad Science Journal, 2019)
This study is designed to detect the level of cytokine IFN-γ concentration, and some antioxidants, including super oxide dismutase (SOD) and Vitamin C, and to estimate the level of sex hormones (FSH and LH), and to determine auto-antibodies (antiphospholipid antibodies (APA) IgG, and anticardiolipin antibodies (ACA) IgG) and to estimate the blood parameters in 51 miscarriage women infected with T.gondii distributed depending on the type of antibodies. Additionally, 39 volunteers non-infected with T.gondii included (19 miscarriage women, 10 pregnant women and 10 non-pregnant women). ELISA and spectrophotometer method were used in this study. The results of IFN-γ showed a significant increase)p<0.05) in the level of IFN-γ in women infected with T.gondii compared with volunteer groups. The current study shows a significant difference in the level of hormones, where the concentration of LH hormone increased in married non-pregnant women compared with other groups, while the concentration of FSH hormone increased in toxoplasmosis women compared with volunteer groups. The results of antioxidants showed no significant difference in Vitamin C activity in infected women compared with volunteer groups, while super oxide dismutase (SOD) activity was significantly lower in infected women compared with volunteer groups. The results of autoantibodies showed a significant difference in anticardiolipin antibodies (ACA) IgM level, the highest level was in aborted women infected with acute infection (IgM Ab), while the anticardiolipin antibodies (ACA) IgG level recorded the highest level in aborted women infected with both acute and chronic infection (IgG&IgM)). The results showed no significant difference in antiphospholipid antibodies (APA) IgM level in infected women when compared to the volunteer groups, while the results showed significant difference in antiphospholipid antibodies (APA) IgG level, where the highest concentration was in the volunteer groups (pregnant and non-pregnant married women). The results of blood parameters showed significant differences in differential leucocytes except for Basophils and Monocytes, and the results showed significant differences in differential erythrocytes, HB, PLT, and PCV.